Urgensi Penetapan Pedoman Standar Teknis Green Economy pada Undang-Undang No. 5 Tahun 1999 (RechtJiva, 2024)
Green economy is an important foundation in achieving sustainable development, which integrates economic, environmental and social aspects. Green economy aims to create economic stability through optimizing energy and environmental balance in the production and marketing of green products which contributes to increasing GDP. However, there is no explicit regulation regarding the green economy in business competition law, which creates a legal vacuum. This research aims to examine the relationship between the green economy concept and business competition law, as well as identifying the legal implications of this regulatory vacuum. The method used is normative juridical, which examines relevant legislation and legal theory. The approach used is a statutory and conceptual approach, with data collection techniques through literature studies and primary and secondary legal materials. The research results show that the green economy is implicitly reflected in Articles 2 and 3 of Law no. 5 of 1999, especially through the phrase "public interest". However, this unclear substance has the potential to create inefficiencies in business competition, with challenges such as barriers to entry for new business actors, losses for first movers, and high production costs. This obstacle can trigger cartel practices and economic injustice that benefits large business actors. This research recommends the need for clear guidelines regarding the implementation of green economy technical standards, which balance the interests of business actors and the public interest, in order to prevent monopolies that harm business competition.